2018
DOI: 10.3389/fimmu.2018.00449
|View full text |Cite
|
Sign up to set email alerts
|

Gene Profiling in Patients with Systemic Sclerosis Reveals the Presence of Oncogenic Gene Signatures

Abstract: Systemic sclerosis (SSc) is a rare connective tissue disease characterized by three pathogenetic hallmarks: vasculopathy, dysregulation of the immune system, and fibrosis. A particular feature of SSc is the increased frequency of some types of malignancies, namely breast, lung, and hematological malignancies. Moreover, SSc may also be a paraneoplastic disease, again indicating a strong link between cancer and scleroderma. The reason of this association is still unknown; therefore, we aimed at investigating whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 96 publications
4
37
1
Order By: Relevance
“…Common features may be observed in cancer and scleroderma, with common actors promoting disease development. Strikingly, a recent gene profiling study revealed oncogenic gene patterns in SSc (77). As abovementioned, the implication of EMT in both diseases is particularly interesting and may originate from common genetic and epigenetic alterations, involving telomere shortening, chromosomal instability, senescence, increased proliferation rates, immune deregulation, and impaired cell metabolism.…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosismentioning
confidence: 99%
See 3 more Smart Citations
“…Common features may be observed in cancer and scleroderma, with common actors promoting disease development. Strikingly, a recent gene profiling study revealed oncogenic gene patterns in SSc (77). As abovementioned, the implication of EMT in both diseases is particularly interesting and may originate from common genetic and epigenetic alterations, involving telomere shortening, chromosomal instability, senescence, increased proliferation rates, immune deregulation, and impaired cell metabolism.…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosismentioning
confidence: 99%
“…Third, numerous microRNAs, including miR-21, miR-29 family and let-7d, have been reported to play key roles in the pathogenesis of cancer and fibrosis, and could even represent potential therapeutic targets in both diseases (77). In SSc, their effects concern collagen gene expression in fibroblasts, collagen degradation, thus extracellular matrix remodeling, apoptosis, and epithelial-mesenchymal transition.…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…Another miRNA which has been found to be overexpressed in the serum, affected skin and explanted fibroblasts from SSc patients is miR-155. [85][86][87] Moreover, it has recently been demonstrated that in SSc fibroblasts the activation of the NOD, LRR and pyrin domain-containing 3 (NLRP3) inflammasome drives miR-155 expression via IL-1 autocrine signaling, that further enhances IL-1 transcription leading to increased collagen production and consequent fibrosis. 87 Besides collagen, miRNAs are also thought to contribute to the regulation of other SSc-related molecules or cytokines.…”
Section: Non-coding Rnasmentioning
confidence: 99%